Radon as a possible indicator of West Antarctic seismicity - Liashchuk, O.; Andrushchenko, Yu.; Liashchuk, L. (Ukrainian Antarctic Journal, 2020)
The measurements of near-surface radon concentration have been carried out at the Ukrainian Antarctic Akademik Vernadsky station (Akademik Vernadsky station) since 2003. Abnormal concentrations of radon could serve as a possible valuable indicator of tectonic activity, along with other evidence, potential signs of an expected earthquake. The aim of the work is to find the relationship between the abnormal values of the surface radon concentration, which correlate with tectonic activity. During the measurements, dosimetric methods for detecting the decay of isotopes and daughter products were used. When analyzing the data, statistical analysis methods were used. The sequence of earthquakes that occurred during instrumental observations of radon concentration, has been analyzed. The potential seismic regions affecting the location of the Akademik Vernadsky station were determined. The distances were determined at which geophysical anomalies are likely to occur within the framework of the proposed model and the expected effect of seismicity on the radon yield at the observation site is estimated. The result of the studies shows low correlation between the concentration of radon at the observation point and tectonic activity in the region at distances up to 1100 km with a magnitude of M > 7. At shorter distances to an earthquake, radon anomalies can be expected at M > 6. In some cases, the increase in radon concentration in day–two before the earthquake has been observed. That can be used as a potential predictor, however, no stable recurrence of such events was measured. It is noted that for the correct interpretation of the radon concentration measurements, the analysis of meteorological parameters can be necessary.